2019
DOI: 10.1038/s41560-019-0404-4
|View full text |Cite
|
Sign up to set email alerts
|

Direct magnetic enhancement of electrocatalytic water oxidation in alkaline media

Abstract: Industrially profitable water splitting is one of the great challenges in the development of a viable and sustainable hydrogen economy. Alkaline electrolysers using Earth-abundant catalysts remain the most economically viable route to electrolytic hydrogen, but improved efficiency is desirable. Recently, electron spin polarization was described as a potential way to improve water-splitting catalysis. Here, we report the significant enhancement of alkaline water electrolysis when a moderate magnetic field (≤450… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
460
3
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 513 publications
(510 citation statements)
references
References 48 publications
(41 reference statements)
14
460
3
6
Order By: Relevance
“…The magenetisms from spin‐up Co 2+ layer and Co 2+ spin‐down layer are canncelled by each other, resulting in zero net magnetism. The enhancement of OER catalytic actvity by magnetic field was recently reported by Galán‐Mascarós et al The finding showed that the magnetic enhancement of catalysts' OER activity has certain coorelation to the catalysts' bulk magnetization. Under moderate magnetic field, materials with higher bulk magnetization exhibit larger enhancement of their OER activities .…”
mentioning
confidence: 57%
See 3 more Smart Citations
“…The magenetisms from spin‐up Co 2+ layer and Co 2+ spin‐down layer are canncelled by each other, resulting in zero net magnetism. The enhancement of OER catalytic actvity by magnetic field was recently reported by Galán‐Mascarós et al The finding showed that the magnetic enhancement of catalysts' OER activity has certain coorelation to the catalysts' bulk magnetization. Under moderate magnetic field, materials with higher bulk magnetization exhibit larger enhancement of their OER activities .…”
mentioning
confidence: 57%
“…The enhancement of OER catalytic actvity by magnetic field was recently reported by Galán‐Mascarós et al The finding showed that the magnetic enhancement of catalysts' OER activity has certain coorelation to the catalysts' bulk magnetization. Under moderate magnetic field, materials with higher bulk magnetization exhibit larger enhancement of their OER activities . Therefore, we investigated the effect of an external magnetic field on LiCoVO 4 and ZnCo 2 O 4 by applying a 250 mT magnetic field during chronoamperometry measurement.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…11,12 An alternative strategy for catalytic reaction control proposes a dynamic catalytic surface, whereby the binding energy (i.e., heat of adsorption) of surface intermediates and associated transition state energies oscillate on the time scale of the catalytic turnover frequency. 13 The heat of adsorption of hydrocarbons on metals and metal oxides can be altered by several methods 14,15 including electric and magnetic elds, [16][17][18][19] photocatalysis, 20 surface strain, 21,22 solid electrolytes, [23][24][25][26][27] catalytic diodes, [28][29][30] and back-gated eld effect modulation. [31][32][33] For each combination of catalyst material, chemical mechanism, and method of external stimulus, the dynamic variables including imposed surface binding energy frequency f and amplitude DU comprise a narrow set of conditions which can potentially achieve catalytic turnover frequencies which are orders of magnitude above the static Sabatier maximum (i.e., Balandin-Sabatier volcano peak).…”
Section: Introductionmentioning
confidence: 99%